Pilot Study to Assess Outcomes of a Drug Allergy Clarification Service on a General Medicine Floor at a Local Community Hospital - Crystal Deas; C. Whitney White (University of Minnesota Libraries Publishing, 2018)
Purpose: Drug allergy documentation in the patient medical record varies in level of detail, and drug intolerances are often inappropriately documented as an allergy in the medical record. A pilot study was conducted to determine the impact of a pharmacy-led drug allergy clarification service. Methods: The pilot quality improvement service was implemented in Fall 2016. General medicine patients were identified through daily census reporting and the electronic medical record (EMR) was reviewed within 72 hours of admission for documented drug allergies and/or intolerances. Patients were interviewed by a clinical pharmacist or a fourth year pharmacy student to determine a complete drug allergy and intolerance history.  Results: A total of 55 patients were interviewed and received the pilot service. A drug allergy/intolerance was documented in EMR for 54.5% (n=30) of patients interviewed. Of those 30 patients, 96.6% (n=29) were noted to have at least one discrepancy between EMR documentation and patient interview. The primary discrepancy noted was drug allergies or intolerances documented in the EMR without a description of the reaction. Conclusion: A pharmacy-led drug allergy clarification service was effective in identifying and clarifying EMR documentation of patients' drug allergies and intolerances. Patients with incorrect or incomplete allergy documentation may receive alternative therapy, which could increase costs and lead to unwanted adverse effects or less effective treatment. As a result of the pilot study, the program has remained in effect and is being expanded to other units within the institution. Article Type: Original Research